BISPHOSPHONATE - RELATED MUCOSITIS (BRM): A CASE REPORT - Pavel Stanimirov; Milena Petkova (Peytchinski Publishing, 2017)
Bisphosphonates (BPs) are the most widely used and effective antiresorptive agents for the treatment of diseases in which there is an increase in osteoclastic resorption, including post-menopausal osteoporosis, Paget's disease, and tumor-associated osteolysis. Oral and maxillofacial surgeons are well aware of the side effects of bisphosphonates and mainly with bisphosphonate-related osteonecrosis of the jaws (BRONJ). Less known are the mucosal lesions associated with the use of these agents. In the scientific literature, there are only few reports of mucosal lesions due to the direct contact of the oral form of BPs with the mucosa (bisphosphonate-related mucositis). They are mostly related to improper use of bisphosphonate tablets that are chewed, sucked or allowed to melt in the mouth before swallowing. Lesions are atypical and need to be differentiated from other mucosal erosions. We present a case of bisphosphonate-related mucositis due to the improper use of alendronate.